2021
DOI: 10.1111/jog.14693
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of survival outcomes between laparoscopic surgery and abdominal surgery for radical hysterectomy as primary treatment in patients with stage IB2/IIA2 cervical cancer

Abstract: Objective To investigate the long‐term oncological outcomes of laparoscopic radical hysterectomy (LRH) and abdominal radical hysterectomy (ARH) for the treatment of stage IB2/IIA2 cervical cancer without preoperative adjuvant therapy. Methods We conducted a multicenter, retrospective, case‐matching study. The differences in overall survival (OS) and disease‐free survival (DFS) between the LRH and ARH were compared under the conditions of real‐world study and case–control matching (1:1 matching). Results There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…From then on, NCCN Guidelines recommend abdominal surgery as the classic hallmark surgery for CC. To date, a few small-size retrospective studies with high-level evidence lacking have declared no significant difference in prognosis between laparoscopic and abdominal RS for LACC patients [ 10 11 12 13 14 15 16 ]. Therefore, to address the above clinical dilemma and provide a higher level of evidence during clinical decision making, we conducted this prospective, multi-center RCT focusing on patients with specific LACC, to compare the differences in prognosis and QoL of these patients receiving different treatment modalities, to further formulate the optimal treatment plan as well as surgical strategy under strict tumor-free principle for specific LACC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From then on, NCCN Guidelines recommend abdominal surgery as the classic hallmark surgery for CC. To date, a few small-size retrospective studies with high-level evidence lacking have declared no significant difference in prognosis between laparoscopic and abdominal RS for LACC patients [ 10 11 12 13 14 15 16 ]. Therefore, to address the above clinical dilemma and provide a higher level of evidence during clinical decision making, we conducted this prospective, multi-center RCT focusing on patients with specific LACC, to compare the differences in prognosis and QoL of these patients receiving different treatment modalities, to further formulate the optimal treatment plan as well as surgical strategy under strict tumor-free principle for specific LACC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the conclusions of the Laparoscopic Approach to Cervical Cancer trail need to be further validated by more clinical trials over time. To date, only a few studies have compared surgical and oncologic outcomes between laparoscopic and abdominal RS in LACC patients [ 10 11 12 13 14 15 16 17 ]. These studies have shown that there is no significant difference in prognosis between laparoscopic and abdominal surgery when using Non-touch Isolation Technique.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 For the diagnosis and treatment of cervical cancer, not only we must follow the basic principles of diagnosis and treatment guidelines, but also pay attention to individualized treatment, so the choice of specific treatment plan often requires the comprehensive judgment of clinicians. 31 The results of clinical studies [32][33][34] so far have shown that for patients with early stage of cervical cancer FIGO clinical stage compared with radiotherapy alone, surgical treatment has the advantages of reducing the mortality rate of cervical cancer and the probability of tumor recurrence, and improving the quality of life of patients after surgery. At the same time, the possibility of permanent damage to ovarian function and other normal organs around the tumor by radiation therapy should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of cervical cancer should be based on the patient’s age, general condition, tumor stage, histologic type, lymph node metastasis, and fertility requirements to formulate the best treatment plan 29,30. For the diagnosis and treatment of cervical cancer, not only we must follow the basic principles of diagnosis and treatment guidelines, but also pay attention to individualized treatment, so the choice of specific treatment plan often requires the comprehensive judgment of clinicians 31. The results of clinical studies32–34 so far have shown that for patients with early stage of cervical cancer FIGO clinical stage compared with radiotherapy alone, surgical treatment has the advantages of reducing the mortality rate of cervical cancer and the probability of tumor recurrence, and improving the quality of life of patients after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In Table 2, we present a list of papers from January 2019 to February 2022 describing more than 20 ARH versus MISRH cases that excluded stage IIB tumors. Up until 2018, almost all papers stated that MISRH had oncological noninferiority to ARH, but from 2019 onward, numerous papers have indicated inferiority for MIRH in terms of outcomes 5–8,17–19,21–42 …”
Section: Introductionmentioning
confidence: 99%